Construcción de un tablero didáctico de lámparas de alumbrado público equipado con sistemas de protección y medición. - Quevedo Herrera, Fernando Mariano (2014)
This research is inclined fundamentally to the development about a didactic board of lamps public lighting equipped with Protective and Measuring systems for the electricity laboratory. All the electric items are mounted on the wood board which allows us an acceptable stability for easy manipulation thereof and reducing by this way at 100% the factors that could cause an electric flaw, the lamps are important items that allows transforming the electric energy at luminous energy which go mounted of a most efficient and safe way allowing do measurements as luminous flux, light intensity, comparing its yield and efficiency between them, assimilating by this way implanted knowledge, the maneuver apparatus, measuring and protection as a voltmeter, ammeter, light meter, thermomagnetic wall plugs, they will be adding to the efficiency’s work of the items to use within the project, facilitating pose parameters of functionality with an admissible percent of the effectiveness during practice to develop. Technologically the research project contributes to the better performance and learning of students in the specialty of electricity.